A Focusing Window Selection Based on Gray-scale Projection - GAO Wei-ning; MA Shan-tao; HE Yong-jun; XIE Yi-ning (Journal of Harbin University of Science and Technology, 2021)
In recent year， automatic microscope imaging technology has been widely used in the field of automatic reading. The selection of focusing window is a key technology in the autofocus algorithm, which directly affects the performance of autofocus algorithm. Traditional focusing window selection method selects fixed position and fixed size area to calculate the sha1pness function, which is inefficient and prone to focus failure. In order to solve this problem, a focus window selection method based on image 护·ay projection is proposed. In this method, gray projection method and adaptive mean inte1val search algorithm are used to determine the focusing window. This method first calculates the gray-scale projection along the coordinate axis. Then this method finds the appropriate subinterval by the self-adaptive mean interval search algorithm. According to the location of the subinte1val in the coordinate axis, a focusing window with accurate position and size is const11Jcted. Experiments show that the grayscale projection window method can track the main area which deviates from the center. It is a self-adaptive window selection method, which can significantly improve the accuracy and speed of auto focusing.